Species composition of the weed component of potato agrocenosis - Saiuk, O. A.; Troiachenko, R. M.; Pavliuk , I. O. (Scientific Progress & Innovations, 2019)
The purpose of the article is studying species and quantity composition of the weed component of potato agrocenosis in the conditions of Cherniakhivskyi district of Zhytomyr region. Methods of research. In the process of the research, the following scientific methods were used: analysis and synthesis (determining the actual weed infestation of potato plantings, species composition of weeds); theoretical search and abstract-logical (theoretical generalizations and formulation of conclusions); graphic (reflecting the research results graphically). The research results. The research results as to the species composition of the weed component of potato agrocenosis and its development during the crop vegetation period have been presented in the article. The research has been carried out by quantitative calculating the number of weeds during potato vegetation and determining their species composition. It has been established that weed synusia of potato plantings are represented by annual late spring species (63.2 %). During potato plants vegetation, the increase in the degree of weed infestation of potato agrocenosis from 9.9 pcs./m2 (in the phase of sprouts) to 49.9 pcs./m2 (before harvesting) has been observed. The elements of scientific novelty. The species and quantity composition of the weed component of potato agrocenosis and its development during the crop vegetation has been established. Practical significance. The knowledge of the species weed composition of in potato planting, the terms of their germination, the quantitative composition of the studied harmful organism will make it possible to use the most effective measures to regulate the number of weeds in order to obtain maximal yield.